New pest threatens food stocks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Since the end of the 1970s a new insect pest, Prostephanus truncatus, has been ravaging food stocks in some African countries. Introduced from Central America, where it attacks mostly maize, it can destroy up to 30 % of stored maize, cassava and,...